STRATEGI ORANG TUA ANGKAT DALAM MEMBINA AKHLAK ANAK DI RUMAH YATIM AR-RAYHAN CURUP - Silvia Erika Putri; Rafia Arcanita; Wandi Syahindra (INCARE, International Journal of Educational Resources, 2020)
This study aimed at finding out a portrayal of the foster or adoptive parents’ strategies in building children's morals at the Ar-Rayhan orphanage of Curup, Bengkulu, using a qualitative approach. The subjects of this study were the foster parents at the orphanage, while the data were collected by means of observation, interviews, and documentation. The data of this study were analyzed by some stages comprising reduction, presentation, and conclusion. This study concluded that the foster parents’ strategies in developing children's morals at the Ar-Rayhan orphanage of Curup extended to: teaching children to get up at dawn and continuously involving them into subuh congregational prayer. After prayer, they were given spiritual activities and a sort of motivation for the children at the Ar-Rayhan Orphanage so that everything they underwent daily would lead to betterment.